A Comprehensive Literature Review of Palliative Care Interventions for Surgical Patients - Yosua Kurnia, Yosua Kurnia; Margaretha, Margaretha (International Medical Journal Corp. Ltd, 2024)
Background: The literature on palliative care interventions for surgical patients demonstrates a growing recognition of the complexities and unique needs of this population. The interdisciplinary nature of palliative care, as highlighted by (Li et al., 2016), underscores the necessity of improving quality of life (QOL) for patients with serious illnesses, while also addressing the methodological challenges in evaluating treatment efficacy. This foundational work emphasizes the importance of innovative analytic approaches to understand longitudinal QOL trajectories, which can ultimately guide clinical practice in palliative settings. Literature Review: The exploration of innovative care models, such as the Perioperative Surgical Home and Enhanced Recovery After Surgery, by (G. Harrison et al., 2021) suggests that these frameworks can enhance care coordination and improve patient outcomes during the perioperative period. Similarly, (C. Ferre et al., 2022) emphasize the importance of implementing palliative care programs in trauma and emergency settings to address the immediate needs of surgical patients. The holistic understanding of total pain in oncologic palliative care, presented by (Aparecida Gomes-Ferraz et al., 2022), stresses the necessity of addressing not only physical pain but also emotional distress through a multidisciplinary team approach. This aligns with the findings of (Lee et al., 2024), who call for a more coordinated approach to interventional procedures for managing cancer pain, highlighting the barriers to optimal pain management in this diverse population. Conclusion: In conclusion, the reviewed literature collectively underscores the importance of innovative, multidisciplinary approaches to palliative care interventions for surgical patients. There is a clear need for comprehensive strategies that address the unique challenges faced by this population, focusing on improving pain management, enhancing quality of life, and fostering effective interdisciplinary collaboration. The evolving landscape of palliative care necessitates ongoing research and practice improvements to ensure that surgical patients receive holistic and effective care throughout their treatment journey.